2008
DOI: 10.1038/emboj.2008.37
|View full text |Cite
|
Sign up to set email alerts
|

Munc18a controls SNARE assembly through its interaction with the syntaxin N-peptide

Abstract: Sec1/Munc18-like (SM) proteins functionally interact with SNARE proteins in vesicular fusion. Despite their high sequence conservation, structurally disparate binding modes for SM proteins with syntaxins have been observed. Several SM proteins appear to bind only to a short peptide present at the N terminus of syntaxin, designated the N-peptide, while Munc18a binds to a 'closed' conformation formed by the remaining portion of syntaxin 1a. Here, we show that the syntaxin 16 N-peptide binds to the SM protein Vps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

74
675
3
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 265 publications
(755 citation statements)
references
References 49 publications
(118 reference statements)
74
675
3
3
Order By: Relevance
“…7 Domain-3 together with domain-1 of STXBP1 form the central cavity providing surfaces for Syntaxin-1 binding, an essential step for SNARE complex assembly and subsequent neurotransmitter release. 3,8 No other amino acid altering or splicing mutations were identified in STXBP1 in the remaining patients. We previously sequenced STXBP1 in healthy French Canadian controls (n¼190) and did not identify any amino acid changing or splicing mutations.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…7 Domain-3 together with domain-1 of STXBP1 form the central cavity providing surfaces for Syntaxin-1 binding, an essential step for SNARE complex assembly and subsequent neurotransmitter release. 3,8 No other amino acid altering or splicing mutations were identified in STXBP1 in the remaining patients. We previously sequenced STXBP1 in healthy French Canadian controls (n¼190) and did not identify any amino acid changing or splicing mutations.…”
Section: Resultsmentioning
confidence: 94%
“…This process is mediated by a complex composed of SNARE proteins and of Munc18-1/STXBP1. [3][4][5] Consistent with its important role for neurotransmission, recent studies showed that mutations in STXBP1 cause severe ID and epilepsy. 6,7 Using array genomic hybridization, Saitsu et al 6 identified a de novo 2 Mb deletion encompassing STXBP1 in a patient with Ohtahara syndrome, an infantile form of epileptic encephalopathy characterized by burst suppressions and severe ID.…”
Section: Introductionmentioning
confidence: 92%
“…Similarly, low-resolution solution scattering models of mouse Munc18a complexed with a soluble C-terminally truncated Sx1a supported a closed binding mode (Colbert et al, 2013). This interaction, which is not compatible with SNARE-complex formation, points to a role for Munc18a as an inhibitor of membrane fusion (Misura et al, 2000;Burkhardt et al, 2008;Chen et al, 2008;Ma et al, 2011). However, other studies have drawn another conclusion: that Munc18 binds open Sx.…”
Section: Introductionmentioning
confidence: 95%
“…2. Crystal structures of three Munc18:Sx systems have been determined: rat Munc18a:Sx1a (Burkhardt et al 2008), rat Munc18a:Sx1aÁN (Colbert et al, 2013) and a primordial Unc18:Sx1a complex from Monosiga brevicollis (Burkhardt et al, 2011). These crystal structures show the same closed Sxbinding mode when a soluble C-terminally truncated form of Sx1a was used to generate crystals.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation